Assessing chemical pollution with biomonitoring approaches in streams and rivers: a critical review - Ariane Moulinec; Jens Arle; Henner Hollert; Sarah Hörchner; Sarah Johann; Cornelia Kienle; Matthias Oetken; Andrea Sundermann (Environmental Sciences Europe)
Abstract Many rivers and streams are affected by chemical pollution, yet current chemical monitoring methods are limited for technical and economic reasons. Biomonitoring has been increasingly used as a means of assessing the impacts of chemical pollution and indirectly monitoring river contamination. To provide an overview of the wide variety of biomonitoring approaches, we conducted a systematic review of the literature investigating the relationship between chemical pollution and biological responses. We distinguished five main approaches for the biomonitoring of chemical pollution: (i) monitoring of native communities; (ii) laboratory bioassays; (iii) in situ bioassays; (iv) mesocosms; and (v) monitoring of wild populations. Although each of them covers a wide range of methods and endpoints, we have highlighted their main advantages and limitations. Because native communities are exposed to a wide range of stressors, isolating the effects of chemical pollution alone is often limited. Most of the existing community indices cannot depict the full extent of the impact of pollutants on communities, but rather provide information on either general degradation of water and/or sediment quality. Effect-based methods (EBMs), including ecotoxicological bioassays and biomarkers, can better isolate the effects of pollution, and, to some extent, of specific types of pollutants. The experimental design of EBMs must be adapted to the research question and the context of the study, so that the test organisms, exposure scenarios and endpoints accurately reflect the contamination. In this context, a comparison with theoretically non-stressful situations with either a dilution series of the exposure solution in the laboratory or a comparison of laboratory and field treatment is relevant. The main difficulties encountered in the approaches investigated in the present review are the comparability of sampling strategies, non-linear concentration–response relationships, extrapolation from laboratory to field exposure, the highly variable sensitivity of organisms and the geographical specificities. Overall, a combination of different EBMs can integrate the effects of exposure to specific contaminants at both spatial and temporal scales while accounting for confounding factors. The establishment of thresholds and guidelines would facilitate the integration of EBMs into regular monitoring programmes. This in turn will greatly facilitate the assessment of chemical impairment.